2008
DOI: 10.1007/s11095-008-9781-2
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Effects of Genetic Polymorphism on the Pharmacokinetics of CYP2C9 Substrates from In Vitro Data

Abstract: This theoretical method well estimated the quantitative changes in pharmacokinetics of CYP2C9 substrates in subjects with mutated alleles of CYP2C9. This can be applied to drug development even from the early clinical phases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 90 publications
3
36
0
1
Order By: Relevance
“…It appears that expressed CYP2B6 protein may be superior to HLMs in IVIVE, especially for the prediction in individuals with reduced-function alleles. However, variable successes were obtained using data from expressed cytochrome P450s, e.g., CYP2C9 (Dickinson et al, 2007a;Kusama et al, 2009), CYP2D6 (Dickinson et al, 2007b), and CYP2B6 (Siccardi et al, 2012). Therefore, the selection of a relevant in vitro system may be dependent on the specific cytochrome P450 isoform and variant allele studied.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that expressed CYP2B6 protein may be superior to HLMs in IVIVE, especially for the prediction in individuals with reduced-function alleles. However, variable successes were obtained using data from expressed cytochrome P450s, e.g., CYP2C9 (Dickinson et al, 2007a;Kusama et al, 2009), CYP2D6 (Dickinson et al, 2007b), and CYP2B6 (Siccardi et al, 2012). Therefore, the selection of a relevant in vitro system may be dependent on the specific cytochrome P450 isoform and variant allele studied.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8] The presence of polymorphic alleles of CYP2C9 decreases the S-warfarin metabolic rate resulting in increased levels of Swarfarin which in turn leads to lower doses of warfarin required to produce the therapeutic response without any bleeding risk. 6,9,10 The reported studies have demonstrated that VKORC1 and CYP2C9 gene variants together with demographic factors account for 50% to 60% variance in warfarin dose requirement. [10][11][12][13] Different dosing algorithms have been constructed from data including demographic factors along with the frequencies of common CYP2C9 and VKORC1 genotypes in their populations.…”
Section: Introductionmentioning
confidence: 99%
“…For example, variability imposed by allelic variants of CYP2C9 with decreased catalytic activity can be addressed in both Caucasian and Asian populations based on successful IVIVE (32,176). By linking the PK model that incorporates genetic variability in CYP2C9 to an indirect pharmacodynamic model of the anticoagulant effect of S-warfarin, Dickinson et al (177) were able to assess the power of published pharmacogenetic studies to show differences between the genotypes in both kinetics and clinical response.…”
Section: Prediction Of the Effects Of Geneticsmentioning
confidence: 99%